THE ECONOMIC BURDEN OF FRAILTY AMONG ELDERLY PEOPLE: A REVIEW OF THE CURRENT LITERATURE - Alkhodary A. A.; Syed Mohamed Aljunid; Ismail, Aniza; Nur A. M.; Shahar S. (Malaysian Journal of Public Health Medicine, 2020)
Life expectancy from birth is increasing dramatically. Due to this increase, the population of elderly people will increase. Consequently, geriatric related illnesses will increase leading to increased necessity to build up comprehensive and coordinated cost effective health care services appropriate for elderly people. Frailty is not a disease, but rather considered as a syndrome requiring comprehensive and multidisciplinary care approach. It is a prevalent reversible pathological transitional stage between healthy aging and disability. Frailty is associated significantly with increased health care utilization, mortality, and comorbidities such falls, hospitalizations, physical dependence, and poor perception of health. The aim of this review is to compile existing literature on the economic cost of frailty syndrome among elderly people in the recent years. Search queries were constructed to look for articles related to the economic cost of frailty in the electronic databases available at the National University of Malaysia library for articles published between the years 2011 and 2019. The accessed electronic database included New England journal of medicine, Science Direct, SCOPUS, BMJ, Cochrane, and Wiley Online Library. Articles included in this review when they were original research, participants were defined as frail elderly, manuscripts written in English language, and involved clearly described measures of frailty cost. Among the literature, twenty one articles were found to satisfy the inclusion criteria of the review process. The cost of care for frail elderly was ranging from US 8,620 to 29,910 per patient per year. The cost of health care was ranging from US 2,540 to 221,400. The health care cost was accounting for 40% to 76% of the total care cost. Hospitalization cost was the highest, it was ranging from US 806 to 152,726. Outpatient cost was ranging from US 200 to 18,000. Medications cost was ranging from US 7 to 3,434 per frail elderly patient per year. Home help cost was ranging from US 804 to 19,728 per frail elderly patient per year. In conclusion, frailty is a costly syndrome. It can be considered as a cost effective target for health promoting interventions to contain future elderly cost.